Translation in the Teaching of a Foreign Language As a Means and As an End - Suparmin Suparmin (TEFLIN, 2002)
Abstract: In the history of foreign language teaching translation has alternately been praised and condemned. Unfortunately, the praise and condemnation were based on a rather simplistic, biased, and extreme view of the role of translation. In this view no clear, explicit distinction was made between translation as a means and as an end although in practice people already showed a tendency to be more concerned with one aspect than the other. Moreover, in their treatment of translation people tended to take an